Networks in automotive systems: the potential for Optical Wireless integration - Green, Roger J.; Rihawi, Zeina; Abdul Mutalip, Zaiton; Leeson, Mark S. (2012)
Vehicular communications become an attraction field to researchers in different sectors; from electronic systems passing by communication technologies and automotive control systems to network topology developers. Control, audio and video signals are transmitted in vehicle using wired and wireless networks. Optical Wireless (OW) technology started to be used in intra-satellite links and aircrafts since it offers high bandwidth and resistance to electromagnetic interference. As more electronic systems were used in vehicle, the EM interference exist, especially in the engine compartment, thus the attraction is directed to use OW in cars. In this paper, a review about control and multimedia systems in vehicles is presented. Overview of implementing OW in vehicles for future automotive communication technologies will also be discussed.